Social Media-Based Entrepreneurial Learning and Its Impact on Opportunity Recognition and Business Model Innovation: Evidence from University Students in Indonesia - Candra Aeni (STAI Hubbulwathan Duri, 2025)
Social media has emerged as a dynamic learning environment for aspiring entrepreneurs, particularly among university students. However, empirical studies on how social-media-based learning influences entrepreneurial competencies such as opportunity recognition and business model innovation remain limited. This study employed a quantitative, explanatory design to examine the relationships among social media–based entrepreneurial learning (SMBEL), opportunity recognition (OR), and business model innovation (BMI) among university students in East Java, Indonesia. Data were collected via an online survey from 202 undergraduate students who had exposure to entrepreneurship education and used social media for entrepreneurial purposes. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for data analysis. Findings revealed that SMBEL has a strong positive effect on OR (β = 0.58, p 0.001) and a smaller but significant direct effect on BMI (β = 0.26, p = 0.001). OR also significantly affects BMI (β = 0.43, p 0.001) and partially mediates the relationship between SMBEL and BMI (β = 0.25, p 0.001). The model accounts for 34% of the variance in OR and 47% in BMI, indicating moderate explanatory power. These results suggest that social media, when purposefully used for entrepreneurial learning, can enhance students’ cognitive ability to recognize opportunities and stimulate innovative thinking in business model development. The study underscores the need for integrating social media into entrepreneurship education strategies to support student-led innovation and opportunity-driven ventures.